Solvent–free and Selective Autooxidation of Alkylbenzenes Catalyzed by Co/NHPI under Phase Transfer Conditions. Issue 13 (24th August 2016) - Patil, Rajendra D; Fuchs, Batya; Taha, Nimer; Sasson, Yoel
Abstract: Solvent‐free, selective and sustainable reaction protocol for an autoxidation of alkylbenzenes catalyzed by Co‐NHPI (Cobalt‐N‐hydroxyphthalimide) under PTC (Phase Transfer Conditions) is described. A multigram scale preparation of acetophenone from ethylbenzene oxidation is demonstrated. The effect of catalyst [Cobalt, DDAB (Di‐n‐decyl‐di‐methyl ammonium bromide) and NHPI] concentrations, different types of catalysts, effect of temperature and oxygen pressure as well as reaction kinetics related to present auto‐oxidation of alkylbezenes is studied in details. Light microscope image shows that DDAB has Multi Lamellar Vesicles (MLVs) structures through which it protects NHPI at high temperatures. Thus efficient recovery and reuse of present ternary catalytic system (Co‐NHPI/DDAB) is feasible. Abstract : The present Co‐NHPI/DDAB ternary catalytic system for an oxidation of alkyl benzenes is mild, high atom yield, and solvent free process. The integrated catalyst is fully reusable and recyclable, and the process does not release any harmful by‐products. The reaction kinetics can be simply and clearly explained.